Synchronization of the coupled FitzHugh-Nagumo systems - Uçar, A; Lonngren, KE; Bai, EW (Pergamon-Elsevier Science Ltd, 2004)
Buric and Todorovic recently studied the coupling of FitzHugh-Nagumo equations that can be used to describe neurological signal propagation. Using techniques from modern control theory, a nonlinear controller is obtained that results in two of the Buric and Todorovic systems being synchronized with each other. The detailed derivation that leads to the controller and numerical results that verify the controller's ability to synchronize the two systems together are included. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Prototype Model; Chaos